Efectos de la defoliación simulada en diversas etapas de desarrollo del algodonero (Gossypium hirsutum L.). - Charris Bolaño, G.; Zúñiga Restrepo, G; Cantillo Morales, S (Santa Marta (Colombia), 1980)
Algodón-Gossypium herbaceum